2016
DOI: 10.1038/nature20121
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of force transmission at bacterial focal adhesion complexes

Abstract: Summary Various rod-shaped bacteria mysteriously glide on surfaces in the absence of appendages such as flagella or pili. In the deltaproteobacterium Myxococcus xanthus, a putative gliding motility machinery (Agl–Glt) localizes to so-called Focal Adhesion sites (FA) that form stationary contact points with the underlying surface. We discovered that the Agl–Glt machinery contains an inner-membrane motor complex that moves intracellularly along a right-handed helical path, and when it becomes stationary at FA si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
192
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(202 citation statements)
references
References 38 publications
4
192
0
Order By: Relevance
“…One possibility is that this machine directly binds and transports lipids, even though there are no obvious lipid binding motifs or cavities found in available structures of the periplasmic components (Carr et al ., ; Deprez C et al ., ). The Tol‐Pal complex is related to the ExbBD‐TonB (Cascales et al ., ; Celia et al ., ), Agl‐Glt (Faure et al ., ) and Mot (Cascales et al ., ; Thormann and Paulick, ) systems, each of which uses pmf‐energized conformational changes to generate force for the uptake of metal‐siderophores, for gliding motility, or to power flagella rotation respectively. In addition, both the Tol‐Pal and ExbBD‐TonB complexes are hijacked by toxins (such as colicins) and bacteriophages to penetrate the OM (Cascales et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that this machine directly binds and transports lipids, even though there are no obvious lipid binding motifs or cavities found in available structures of the periplasmic components (Carr et al ., ; Deprez C et al ., ). The Tol‐Pal complex is related to the ExbBD‐TonB (Cascales et al ., ; Celia et al ., ), Agl‐Glt (Faure et al ., ) and Mot (Cascales et al ., ; Thormann and Paulick, ) systems, each of which uses pmf‐energized conformational changes to generate force for the uptake of metal‐siderophores, for gliding motility, or to power flagella rotation respectively. In addition, both the Tol‐Pal and ExbBD‐TonB complexes are hijacked by toxins (such as colicins) and bacteriophages to penetrate the OM (Cascales et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current model, contact by a T4P on one cell to EPS on a neighboring cell triggers pilus retraction, enhancing the movement of cells within groups (Li et al , ). By contrast, gliding motility promotes the movement of single cells and depends on the Agl/Glt machinery that assembles at the leading cell pole, adheres to the substratum, moves rearwards as cells move and finally disassembles at the lagging cell pole (Zhang et al , ; Faure et al , ; Schumacher and Søgaard‐Andersen, ). LPS O‐antigen has also been implicated in gliding motility (Fink and Zissler, ; Yang et al , ; Yu and Kaiser, ), while Bowden and Kaplan () reported that O‐antigen is not important for gliding.…”
Section: Introductionmentioning
confidence: 99%
“…This proton channel/motor complex is homologous to the Escherichia coli flagella stator complex MotAB (AglR is a MotA homologue while AglQ and AglS are MotB homologues) (Nan et al, 2011;Sun et al, 2011;Nan and Zusman, 2016). The gliding motors in M. xanthus move rapidly along helical trajectories, slow down and assemble into multicomponent gliding complexes at the putative focal adhesion sites, and propagate proton motive force onto the cell surface (Nan et al, 2010b(Nan et al, , 2011(Nan et al, , 2013(Nan et al, , 2014Luciano et al, 2011;Sun et al, 2011;Faure et al, 2016;Nan and Zusman, 2016). M. xanthus coordinates both motility systems to move unidirectionally along the long cell axis (Lenz and Sogaard-Andersen, 2011;Kaimer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%